2005
DOI: 10.1038/nature03659
|View full text |Cite
|
Sign up to set email alerts
|

Notch/γ-secretase inhibition turns proliferative cells in intestinal crypts and adenomas into goblet cells

Abstract: The self-renewing epithelium of the small intestine is ordered into stem/progenitor crypt compartments and differentiated villus compartments. Recent evidence indicates that the Wnt cascade is the dominant force in controlling cell fate along the crypt-villus axis. Here we show a rapid, massive conversion of proliferative crypt cells into post-mitotic goblet cells after conditional removal of the common Notch pathway transcription factor CSL/RBP-J. We obtained a similar phenotype by blocking the Notch cascade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
1,244
3
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,404 publications
(1,319 citation statements)
references
References 29 publications
68
1,244
3
4
Order By: Relevance
“…Notch signaling is essential for maintaining the stem cell niche in various organs 28, 29, 30, 31. Regarding its functions in the liver, it was originally implicated in the regulation of the terminal differentiation of HPCs into biliary epithelial cells23 and/or ductal structure formation in liver development 32, 33, 34.…”
Section: Discussionmentioning
confidence: 99%
“…Notch signaling is essential for maintaining the stem cell niche in various organs 28, 29, 30, 31. Regarding its functions in the liver, it was originally implicated in the regulation of the terminal differentiation of HPCs into biliary epithelial cells23 and/or ductal structure formation in liver development 32, 33, 34.…”
Section: Discussionmentioning
confidence: 99%
“…An example of Notch signaling in vertebrates involved in stem cell maintenance is the intestinal crypt compartment in the gut, a highly proliferative tissue, reviewed in [123]. Post-natal gut specific inactivation of RBP-J results in the complete loss of proliferating transient amplifying (TA) cells [124]. In a reciprocal experiment, expression of activated Notch1 (NICD) in the gut inhibits differentiation of crypt progenitors [125].…”
Section: Notch Signaling In Development and Differentiationmentioning
confidence: 99%
“…Notch signaling plays a key role specifying differentiation in the intestinal epithelium in developing and adult mice [18], [19], [20], [21]. Previously we have shown that conditional expression of an activated Notch mutant fused to Enhanced Green Fluorescent Protein (EGFP) (ICD-E) in the intestine of adult mice results in a transient increase in goblet cells on the villus, within 24 hours of Notch activation, followed by crypt apoptosis and shedding of the recombinant epithelium [20].…”
Section: Introductionmentioning
confidence: 99%